Revision of the bee genus Capicola (Hymenoptera: Apoidea: Melittidae) distributed in the Southwest of Africa - Denis MICHEZ (European Journal of Entomology, 2007)
The bee family Melittidae (Hymenoptera: Apoidea) includes 14 genera. Most have been reviewed but not the small African genus Capicola. The present work aims to fill this gap. Based on the revision of the type material and 1272 additional specimens, we provide a comprehensive synonymic and annotated catalogue of the 12 Capicola species sensu Michener (1981). Lectotypes are designated for the previously established species Capicola braunsiana (= C. obscura syn. n.), C. cinctiventris, C. femorata, C. flavitarsis and C. rufiventris. Moreover, C. danforthi sp. n., C. flavicara sp. n., C. gessorum sp. n., C. micheneri sp. n., and C. richtersveldensis sp. n., are newly described, as well as the previously unknown female of C. nanula, male of C. nigerrima and male of C. rhodostoma. New synonymies are proposed for C. braunsiana (= C. obscura) and C. flavitarsis (= C. cinctiventris). An original dataset of 20 morphological characters is used for the inference of the 12 species' phylogenetic relationship. A key to species is provided. In addition, the ranges of the 12 taxa are mapped and discussed. This paper contributes to a global revision of the Melittidae.